Odpowiedź:
a) 8 + (-6,7) = 1,3
-12 + (-5,3) = -17,3
5,6 + (-3,2) = 2,4
-8,1 + (-7,3) = -15,4
-2,1 + (-4,25) = -6,35
b) -7,12 + 9,36 = 2,24
2,5 + (-4,3) = -1,8
[tex]9 + ( - 3 \frac{1}{4} )= 6 \frac{3}{4} [/tex]
[tex] - 5 \frac{1}{7} + ( - 2\frac{3}{9} ) = - 7 \frac{4}{7} [/tex]
[tex]8 \frac{5}{9} + ( - 3 \frac{1}{9} ) = 5\frac{4}{9} [/tex]
[tex]c) - 4 \frac{3}{8} + ( - 5 \frac{7}{8} ) = - 9 \frac{10}{8} = 10 \frac{2}{8} [/tex] = 10 i 1/4
[tex] - 6 \frac{1}{4} + 8 \frac{3}{4} = 2 \frac{2}{4} [/tex] = 2 i 1/2
[tex] - 2 \frac{1}{6} + ( - 4 \frac{5}{6} ) = - 6 \frac{6}{6} = - 7[/tex]
[tex]9 \frac{1}{6} + ( - 5 \frac{5}{6} ) = 3 \frac{2}{6} [/tex] = 3 i 1/3
[tex] - 7 \frac{2}{9} + 5 \frac{5}{9} = - 1\frac{6}{9} [/tex] = -1 i 2/3
Pozdrawiam.